Research on the photoelectrical properties of TiO2-doped V2O5/FTO nanocomposite thin films under thermal and electrical excitation - Xue Chang; Li Yi; Zhang Haoting; He Weiye; Peng Weiye; Dai Wenyan; Yuan Zhen; Lin Ke; Wang Wei; Shi Zhangqing; Liu Hongwei (Journal of the European Optical Society-Rapid Publications)
The TiO2-doped V2O5/FTO nanocomposite thin films were prepared on the FTO substrates by sol-gel method and post-annealing process, and the MSM structural devices based on the prepared films were fabricated by sputtering, photolithography and etching techniques. SEM, XRD, and XPS were respectively used to study the morphology, structure and composition of the film, and the electrical and optical regulations of the device were measured by using spectrophotometry and semiconductor parameter analyzer. In the temperature range of 20–360 °C, the maximum modulation amplitude of the TiO2-doped V2O5/FTO film in the 400–1600 nm band was 18.282% and the modulation of the V2O5/FTO film was increased by 9.663% after TiO2-doping. The resistance of the FTO/V2O5-TiO2/FTO device reduced by 3–4 orders of magnitude by comparing with the FTO/V2O5/FTO device. The FTO/V2O5-TiO2/FTO device underwent semiconductor-metal state transition (SMT) around 259.91 °C. Under the applied voltage of 0–5 V, the maximum transmittance variations could reach 8.821%, 7.174% and 11.540% in 400–1600 nm band at the temperature of 20 °C, 40 °C and 80 °C, respectively. The outstanding optical and electrical regulation properties and the favorable cycling stability make the nanocomposite film expected to be applied in the field of optoelectronic devices.